KEANEKARAGAMAN SEMUT (Famili Formicidae) PADA LAHAN GAMBUT DI LINGKUNGAN GEDUNG BARU FAKULTAS KEHUTANAN UNIVERSITAS TANJUNGPURA PONTIANAK - Rosa, Nandini; Dewantara, Iswan; Prayogo, Hari (Universitas Tanjungpura, 2019)
Ants have an important role in an ecosystem such as seed spreaders, pollinators, decomposers, and soil growers. Ants can live on peatlands that have acidic pH. The new building of the Faculty of Forestry is an area of peatland where there is one of the fauna, namely ants. The ants in the environment of the Faculty of Forestryâ€™s new biulding are unknown. The research aims to record the types of ants found on peatland in the environment of the new building of the Faculty of Forestry, Tanjungpura University. Takingthe samples of ants was done with sifting hand collecting and leaf litter sifting methods. This study found 4 subfamilies and 7 genera of ants. The subfamilies found were Subfamily Formicinae consisting of the genera Anoplolepis, Camponotus, Echinopla, and Polyrhachis, Subfamily Ponerinae consisting of Genus Diacamma; Subfamily Pseudomyrmecinae consisting of genus Tetraponera; and Subfamily Myrmicinae consisting of the Crematogaster Genus. Diversity index has a value of H Ì… = 1.44 which indicates that the research location has moderate diversity. The overall index of species richness has a DMg value = 5.58 indicating the wealth of ant species is in the high category. Evenness index with a value of 0.73, evenness of ant species is quite even. Â Keywords: Diversity of ants, Faculty of Forestry, Family Formicidae, Peatlands